The Effect of Intermittent Fasting on Insulin Resistance and Lipid Metabolism - Mohamad Arif (The International Science of Health Journal, 2023)
Dietary intervention with intermittent fasting can be a non-pharmacological management option in conditions of insulin resistance, dyslipidemia, and obesity. Intermittent fasting is an example of calorie restriction (not eating and drinking that contains calories) at predetermined times. This intermittent fasting protocol can be divided into time-restricted eating (TRE), alternative day fasting (ADF), or religious fasting. Intermittent fasting increases AMP activated protein kinase (AMPK) and triggers autophagy which has a favorable effect on glucose metabolism, namely lowering blood glucose, plasma insulin levels and homeostasis model assessment of insulin resistance (HOMA-IR). In addition, this fasting can reduce apolipoprotein B, increase apolipoprotein A, and reduce the hormone leptin which affects the decrease of LDL, increase of HDL and weight loss. Additional benefits of intermittent fasting are anti-aging, anti-inflammatory, and anticancer.